The humanities in 2015 : why we need them and how they contribute to being human - Shaughnessy, Michael F. (World philosophy series., 2014)
There is a crisis in the Humanities. This crisis encompasses the definition of the humanities, the depth, breath and scope of the humanities and the fact that the humanities has been diluted by various tangential fields over the last few decades. The authors address the need to recapture the beauty of the humanities, the importance of the humanities and the impact of the humanities on this, and future generations. Scholars in various fields (art, music, etc.) have endeavored to represent their discipline, while at the same time galvanizing the need for a more serious study of the humanities an.